Comparison Between Double Movement Theory and Nazariyyat Al-Hudud Theory on Polygamy Laws - Khairul Hamim (El-Mashlahah, 2022)
The issue of polygamy is one of the issues in Islamic family law which still become a hot, interesting, and updated debated topic to be studied, either in the view of state law or a theme for discussion, under the different interpretations in understanding the verses of the Qur'an. The theme of polygamy has been discussed by scholars in the books of fiqh and their interpretations. But, their views that have developed so far tend to reinforce the opinion that polygamy is permissible based on the text of paragraph 3 of surah al-Nisa. The verse is a source of polemic interpretation, by both classical and contemporary scholars on answering the question of whether polygamy practice is permissible or not. This paper focused on two contemporary scholars, namely Fazlur Rahman and Muhammad Syahrur. They have their views on the polygamy law. This research was normative legal research, using the approach of ushul fiqh and comparative law. The study indicates that Fazlur Rahman, with double movement theory, interprets fairness as a condition for the permissibility of polygamy with love and not material things, such as fairness in physical services. Meanwhile, Muhammad Syahrur, with his boundary theory (nazariyyat al-hudud), interprets fairness as one's ability and obligation to look after, protect and raise orphans from polygamous widows. Apart from that, Syahrur also stated that the widow of being married in polygamy was a widow whose husband had died. The two theories have contributed new colors and the interpretation of Islamic law.